THE IMPLICATIONS OF US-TAIWAN RELATIONS ON US-CHINA RELATIONS UNDER THE OBAMA ADMINISTRATION - Michelle Alysa (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2019)
President Obama served two terms as the US president between 2009-2016. He managed to steer the US into Asia using the Pivot to Asia strategy. The strategy is not only used as a method to spread the US influence, but also to balance the peaceful rise of China. The strategy also includes Taiwan, whom until now is a key leverage against China due to China’s unresolved claim over Taiwan. With the US spread of influence on Asia and Taiwan, US-Taiwan relations impacted US-China relations under the Obama administration. The US-Taiwan bilateral relations become a trigger point to the US-China relations ignited several frictions. This research aims to identify implications and the result of the US-Taiwan relations towards the US-China relations under the Obama administration. Using the explanatory and historical comparative method with qualitative approach, this research indicates that the US and Taiwan relations impacted the US-China bilateral relations in several ways. It resulted in continuous and rising security dilemma, tension, and arms race in Asia. These implications are intensifying the existing differences between the US and China explained through the Offensive and Defensive Realism theories. Despite the unofficial status of Taiwan as a state, its relations to one of the major player in the world can affect the others as long as the three states remain connected.